Synthesis and thermophysical properties of imidazolium-based bronsted acidic ionic liquids - Muhammad, N. (American Chemical Society, 2014)
A range of imidazolium-based Bronsted acidic ionic liquids (ILs) have been synthesized by varying the side chain length of the alkyl and alkyl sulfonic group incorporated to the C1 and C3 positions in the imidazolium ring respectively with a fixed HSO4- anion. The synthesized ILs were characterized using NMR for structure confirmation and CHNS for elemental analysis. The thermal properties such as thermal decomposition temperature were determined using thermogravimetric analysis, and several key physical properties such as viscosity and density were measured within a temperature range of 20 C to 80 C using an Anton Paar viscometer and densitometer. The density measurement results and established equations were used to calculate the molecular volumes, standard entropies, crystal lattice energies, and thermal expansion coefficients of the synthesized ILs. Â© 2014 American Chemical Society.